Junior High School Students' Geometry Ability Based on Van Hiele Level's Thinking - Prismadian Amalia Putri; Subanji; Santi Irawati (UNMUHBABEL PRESS, 2024)
The ability to solve problems and logical thinking of students can be grown by studying Geometry. However, the reality in the field and some research in Indonesia shows that the geometric thinking ability of junior high school students is still relatively low. This study aims to examine the geometric thinking ability of junior high school students according to Van Hiele Theory. This research is a qualitative study with a descriptive approach, which was conducted in one of the junior high schools in Pringsewu Regency involving 28 students of class VIII. One student was selected to represent levels 1, 2, 3, and 4 Van Hiele as the research subject.  Data collection was carried out using multiple choice tests and interviews. Data analysis techniques were conducted with data reduction, data presentation, and conclusion drawing stages. The data originality technique was carried out by triangulation, in which the researcher compared the test data with the results of student interviews. The results showed that level 1 students (28.57%) could recognize and name geometric shapes visually; level 2 students (14.28%) could study geometric shapes by observing and mentioning the properties of the shapes; level 3 students (7.14%) could make connections between various geometric shapes and detect general properties of certain geometry; level 4 students (3.57%) could distinguish and make simple conclusions about the shapes and properties of shapes. Kata kunci: berpikir geometri, level van hiele, siswa SMP.